Notch1 Signaling Contributes to Mechanical Allodynia Associated with Cyclophosphamide-Induced Cystitis by Promoting Microglia Activation and Neuroinflammation - Jialiang Chen; Honglu Ding; Bolong Liu; Xiangfu Zhou; Xin Zhou; Zhijun Lin; Fei Yang; Hailun Zhan; Hengjun Xiao (Hindawi Limited, 2021)
Aims. Notch1 signaling regulates microglia activation, which promotes neuroinflammation. Neuroinflammation plays an essential role in various kinds of pain sensation, including bladder-related pain in bladder pain syndrome/interstitial cystitis (BPS/IC). However, the impact of Notch1 signaling on mechanical allodynia in cyclophosphamide- (CYP-) induced cystitis is unclear. This study is aimed at determining whether and how Notch1 signaling modulates mechanical allodynia of CYP-induced cystitis. Methods. CYP was peritoneally injected to establish a bladder pain syndrome/interstitial cystitis (BPS/IC) rat model. A γ-secretase inhibitor, DAPT, was intrathecally injected to modulate Notch1 signaling indirectly. Mechanical withdrawal threshold in the lower abdomen was measured with von Frey filaments using the up-down method. The expression of Notch1 signaling, Iba-1, OX-42, TNF-α, and IL-1β in the L6-S1 spinal dorsal horn (SDH) was measured with Western blotting analysis and immunofluorescence staining. Results. Notch1 and Notch intracellular domain (NICD) were both upregulated in the SDH of the cystitis group. Moreover, the expression of Notch1 and NICD was negatively correlated with the mechanical withdrawal threshold of the cystitis rats. Furthermore, treatment with DAPT attenuated mechanical allodynia in CYP-induced cystitis and inhibited microglia activation, leading to decreased production of TNF-α and IL-1β. Conclusion. Notch1 signaling contributes to mechanical allodynia associated with CYP-induced cystitis by promoting microglia activation and neuroinflammation. Our study showed that inhibition of Notch1 signaling might have therapeutic value for treating pain symptoms in BPS/IC.